The brain computes dynamic facial movements for emotion categorization using a third pathway - Yuening Yan; Jiayu Zhan; Oliver G. B. Garrod; Robin A. A. Ince; Rachael E. Jack; Philippe G. Schyns (Proceedings of the National Academy of Sciences, 2025)
Emerging theories in cognitive neuroscience propose a third brain pathway dedicated to processing biological motion, alongside the established ventral and dorsal pathways. However, its role in computing dynamic social signals for behavior remains uncharted. Here, participants (N = 10) actively categorized dynamic facial expressions synthesized by a generative model and displayed on different face identities—as “happy,” “surprise,” “fear,” “anger,” “disgust,” “sad”—while we recorded their MEG responses. Using representational interaction measures that link facial features with MEG activity and categorization behavior, we identified within each participant a functional social pathway extending from the occipital cortex to the superior temporal gyrus. This pathway selectively represents, communicates, and integrates facial movements that are essential for the behavioral categorization of emotion, while task-irrelevant identity features are filtered out in the occipital cortex. Our findings uncover how the third pathway selectively computes complex dynamic social signals for emotion categorization in individual participants, offering computational insights into the dynamics of neural activity.